2008
DOI: 10.1111/j.1540-8175.2008.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Echocardiographic Assessment with Standard Doppler and Tissue Doppler Imaging of Left Ventricular Filling Pressure in Idiopathic and Ischemic Dilated Cardiomyopathy

Abstract: In conclusion, ARd in idiopathic and S/D in ischemic DCM might be used as specific additional information to estimate LVFP when E/Ea falls within intermediate range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…By echocardiography it is possible to estimate the LVFP noninvasively, analyzing the mitral inflow velocity and the pulmonary venous flow. [25][26][27] The echocardiographic estimation of LFVP can be influenced by MR. 28 Previous studies have reported on the estimation of mean PCWP by using mitral inflow in patients with MR. 29,30 Although several measurements derived from mitral inflow related well to PCWP, including IVRT, E/A, and DT, the best correlations between Doppler measurements and PCWP were observed in patients without significant MR. 29 Thus, the present study was undertaken to examine whether E/Ea was associated with invasive measures of LVEDP in patients with MR. 18 To overcome these limitations, combinations of the mitral flow velocity curves with TDI parameters have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…By echocardiography it is possible to estimate the LVFP noninvasively, analyzing the mitral inflow velocity and the pulmonary venous flow. [25][26][27] The echocardiographic estimation of LFVP can be influenced by MR. 28 Previous studies have reported on the estimation of mean PCWP by using mitral inflow in patients with MR. 29,30 Although several measurements derived from mitral inflow related well to PCWP, including IVRT, E/A, and DT, the best correlations between Doppler measurements and PCWP were observed in patients without significant MR. 29 Thus, the present study was undertaken to examine whether E/Ea was associated with invasive measures of LVEDP in patients with MR. 18 To overcome these limitations, combinations of the mitral flow velocity curves with TDI parameters have been proposed.…”
Section: Discussionmentioning
confidence: 99%